A Educação Profissional Integrada ao Ensino Médio: avaliação do Curso Técnico Integrado em Petroquímica do IFCE Campus Caucaia - Sousa, Francisco Renato Alves de (2020)
The history of professional education in Brazil runs through many paths and involves political and economic issues. It is a land marked by disputes caused by the transformations of the world of work, in the wake of modern capitalism. It is in this context, that this dissertation sought to reflect on the following question: The Federal Institute of Education, Science and Technology of Ceará, campus Caucaia, in the execution of the Federal Policy of Professional Education Integrated to High School, in full regime, has fulfilled its institutional mission, in particular, in transforming the lives of students graduating from Integrated Technical Course in Petrochemicals? The research adopted the theoretical-political perspective as a methodological path with a critical bias and emphasis on three aspects of analysis: the context of policy formulation, the content of the policy and its institutional trajectory. The research is descriptive, with a qualitative-quantitative approach, and was structured based on the general objective, which was to evaluate the Integrated Technical Course in Petrochemicals at IFCE campus Caucaia as a tool for the socioeconomic transformation of alumni. To achieve this purpose and understand the issues involved in public policy, the following specific objectives were established: to reflect on the capitalist dynamics involving the world of work and professional education based on their theoretical conflicts; to investigate the context, the conceptual framework and the institutional trajectory of vocational education integrated to high school and, finally, to understand the perception of graduates about the possible socioeconomic impacts provided by integrated technical training. The survey results emphasize that professional education integrated with high school cannot be assessed only from quantitative indicators of insertion in the labor market. This public policy produces important qualitative impacts, which translate into successful experiences in the maturation of young people and their preparation to enter higher education. It was concluded that public policy, in the case studied, provides the opening of many horizons and perspectives for young people, but it needs adjustments to enable greater integration with the labor market.